2015
DOI: 10.1128/aem.03697-14
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of Intestinal Ciliates, Including Charonina ventriculi, and Comparison of Microscopy and 18S rRNA Gene Pyrosequencing for Rumen Ciliate Community Structure Analysis

Abstract: bThe development of high-throughput methods, such as the construction of 18S rRNA gene clone or pyrosequencing libraries, has allowed evaluation of ciliate community composition in hundreds of samples from the rumen and other intestinal habitats. However, several genera of mammalian intestinal ciliates have been described based only on morphological features and, to date, have not been identified using molecular methods. Here, we isolated single cells of one of the smallest but widely distributed intestinal ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 62 publications
1
58
0
Order By: Relevance
“…This inconsistency might be due to the difference on the fraction of data being analyzed and on the focus of these studies. Earlier studies were mainly focused on rumen ciliates, and the taxonomic assignment was made based on sequence data generated using ciliate-specific marker gene (Kittelmann et al, 2013;Henderson et al, 2015;Kittelmann et al, 2015;Comtet-Marre et al, 2017). Although the rumen ciliate reference database used in these studies was based on a full-length 18S rRNA gene, it was built for the analysis of Trichostomatia and thus does not contain reference sequences of flagellated protozoa.…”
Section: 1%mentioning
confidence: 99%
See 1 more Smart Citation
“…This inconsistency might be due to the difference on the fraction of data being analyzed and on the focus of these studies. Earlier studies were mainly focused on rumen ciliates, and the taxonomic assignment was made based on sequence data generated using ciliate-specific marker gene (Kittelmann et al, 2013;Henderson et al, 2015;Kittelmann et al, 2015;Comtet-Marre et al, 2017). Although the rumen ciliate reference database used in these studies was based on a full-length 18S rRNA gene, it was built for the analysis of Trichostomatia and thus does not contain reference sequences of flagellated protozoa.…”
Section: 1%mentioning
confidence: 99%
“…A recent survey based on 18S rRNA gene amplicon sequencing revealed that almost all protozoal sequencing data from 742 rumen content samples worldwide were assigned to 12 genus-equivalent protozoal groups, namely, Anoplodinium-Diplodinium, Enoploplastron, Entodinium, Epidinium, Eremoplastron-Diploplastron, Eudiplodinium, Metadinium, Ophryoscolex, Ostracodinium, Polyplastron, Dasytricha, and Isotricha (Henderson et al, 2015). Similar rumen ciliate community structure has also been observed in cattle using high-throughput sequencing and microscopic methods (Kittelmann and Janssen, 2011;Kittelmann et al, 2015). The differences between metatranscriptomic and traditional identification methods further emphasize that more isolated and pure culture-based studies are needed to comprehensively characterize rumen eukaryotic microorganisms.…”
Section: 1%mentioning
confidence: 99%
“…Ciliate protozoal sequences were clustered using the prefix-suffix method (22). Representative OTUs were subjected to BLAST searches against a newly assembled BLAST database composed of the following databases: a modified Greengenes gg_13_5 database, which was depleted of all sequences with taxonomy assignments beginning with "k__Archaea" (26); RIM-DB (25); and databases for intestinal ciliate protozoa (27) and anaerobic fungi (28). Relative abundance tables were generated at the species level (bacteria and archaea) or genus level (ciliate protozoa).…”
Section: Sampling Methods (I) Stomach Tubing (Rumen)mentioning
confidence: 99%
“…Several studies have shown that endosymbiotic methanogens in the genus Methanobrevibacter reside in protozoa species belonging to the family Isotrichidae (Chagan et al ., ; Irbis and Ushida, ), which suggests that different adhesins may be responsible for interactions with this protozoal family. Eudiplodinium maggii appeared to be the dominant protozoal species in the protozoa sample before reverse panning; however, it is possible that this species is overrepresented in the data, as larger protozoa tend to have more 18S rRNA gene copies per genome (Kittelmann et al ., ). Although quantification of protozoa by 18S rRNA gene copies may introduce a bias towards larger protozoa, this does not affect our interpretation of the pyrosequencing data as we compared the relative abundance of protozoal species in two samples that were processed by the same method.…”
Section: Resultsmentioning
confidence: 97%